The Grounding of Hegel's Objective Idealism in the Jena’s Critical Writings - Cannalonga, Francisco Malê; Barbosa, Jonnefer Francisco (Revista Eletrônica Estudos Hegelianos, 2025)
In this paper we set out to outline the main characteristics of Hegel's objective idealism as it emerges in his polemic with the “philosophies of reflection” in the Jena’s critical writings (Jenaer Kritische Schriften). In the introduction we defend the use of the concept of “objective idealism” to characterize Hegelian idealism, above all in function of its ontological direction (as opposed to the epistemological direction of the philosophies of reflection). In the first part, we will analyze Hegel’s critique of the limitations of the theoretical aspects of the “philosophies of reflection”, above all the split between subject and object that they contain and the presupposition of an “empirical world” as its theoretical foundation. Finally, we will analyze how Hegel sees the manifestation of these limitations in the practical philosophies of Kant and Fichte, especially regarding their inability to grasp the fundamental determinations of modern society and the historical dimension that circumscribes its genesis. We conclude that one of the central elements of Hegel's objective idealism lies in his efforts to capture the objective determinations of society and history, something that is impossible when one presupposes a purely empirical way of the world’s structure and unfolding and the separation of subject and object.
Keywords: Idealism; Practical Philosophy; Dialectics; Ontology; Epistemology; Historicity